Effects of Hybrid Corrosion Inhibitor on Mechanical Characteristics, Corrosion Behavior, and Predictive Estimation of Lifespan of Reinforced Concrete Structures - Duc Thanh Tran; Han-Seung Lee; Jitendra Kumar Singh; Hyun-Min Yang; Min-Gu Jeong; Sirui Yan; Izni Syahrizal Ibrahim; Mohd Azreen Bin Mohd Ariffin; Anh-Tuan Le; Anjani Kumar Singh (Buildings)
A fixed ratio amount, i.e., L-arginine (LA) and trisodium phosphate dodecahydrate (TSP) at 2:0.25, is considered as a hybrid inhibitor. This research aims to extensively investigate the impact of utilizing the hybrid corrosion inhibitor on the corrosion resistance properties in accelerated condition, mechanical characteristics, and predictive estimation of the lifespan of reinforced concrete (RC) structures. Various experiments, such as setting time, slump, air content, porosity, compressive strength, and chloride diffusion coefficient, were conducted to elucidate the influence of the hybrid corrosion inhibitor on the mechanical properties of the concrete matrix. Meanwhile, linear polarization resistance (LPR) and electrochemical impedance spectroscopy (EIS) in 10 wt. % NaCl under wet–dry cycles are utilized to assess the corrosion resistance property, corrosion initiation time, and kinetics of the passive film formation on the steel rebar. Alternatively, both deterministic and probabilistic-based predictions of service life by Life 365 software are utilized to demonstrate the efficacy of the hybrid corrosion inhibitor in protecting the steel rebar in RC structures. All the results confirm that the HI-4 mix (LA:TSP = 3.56:0.44) exhibits excellence in preventing the corrosion and extending the service life of RC structures, due to the adsorption of inhibitor molecules and formation of P-Zwitterions-(Cl)-Fe, Zwitterions-(Cl)-Fe, and FePO4 complexes onto the steel rebar surface. However, HI-3 shows the optimal mechanical and electrochemical properties for RC structures.